Evaluation of energy management system of a hybrid energy source in EV - Touileb, Rachid; Abbou, Ahmed (Institute of Advanced Engineering and Science, 2023)
This paper presents a comparative study of different energy management strategies and technologies of fuel-cell hybrid electric vehicles integrating a proton exchange membrane fuel cell device in addition to a lithium-ion battery as a secondary energy source. Therefore, an experimental analysis is carried out to seek the successful hybrid powertrains considering the hydrogen utilization in fuel cells and state-of-charge regulation in Li-ion batteries. Different approaches were simulated using a developed vehicle simulator in MATLAB/Simulink. The simulations were performed using three standard driving cycles in which a second study based on energy management strategies tested was presented and analyzed. Simulation’s results show the superiority and economic success of the proposed technology and method, especially the FSBS and MEPT management strategies due to the successful use of the sources and the significant optimization in terms of hydrogen consumption while maintaining optimal Li-ion battery usage.